Kerangka Pengembangan Strategis untuk TPI Palang dengan Mengintegrasikan Pendekatan SWOT dan QSPM - Dewi Nur Fadhillah; Deviana Diah Probowati; Danang Ananda Yudha (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
TPI Palang is the most significant contributor to capture fisheries production in Tuban, with 55% of the total capture fisheries production in Tuban regency, namely 34,043 tons. However, the infrastructure condition and fluctuations in the selling price of captured fish. This study aims to improve the competitiveness of TPI Palang compared to other TPIs, improve operational efficiency by providing better facilities, improve the quality of catches to meet market standards and support fishermen's welfare through guarantees of competitive fish selling prices. The research was conducted at TPI Palang from October 17 to December 5, 2024. Sampling in this study used an expert sampling technique of 5 expert respondents: The head of the Tuban Regency Fisheries Agency Division, the Head of UPTD TPI, the Administrator, the head of the Fishermen Association, and a Middleman with 10 years of experience. Variables used in this research are financial, operational, human resource, economic, socio-cultural, and technological. The data analysis tools used are SWOT and QSPM methods. The SWOT analysis results: There are five strength factors, four weakness factors, five opportunity factors, and four threat factors. IFAS and EFAS matrix show total scores of 3.09 and 2.75, respectively, which puts TPI Palang in the quadrant IV position, which is at a critical point that requires further development to achieve better growth. QSPM matrix results obtained a TAS value of 6.25 with a priority strategy of improving and completing inadequate TPI facilities and providing BIMTEK to the Fishermen Community to maintain the quality of fishermen. Based on the results of the analysis that has been carried out on the Fish Auction Place Business (TPI). It is expected that the Fish Auction Place Business can carry out a series of strategy implementations well and conceptualize them based on alternatives that have been prioritized using QSPM.